Novel autosomal recessive LAMA3 and PLEC variants underlie junctional epidermolysis bullosa generalized intermediate and epidermolysis bullosa simplex with muscular dystrophy in two consanguineous families. (1st August 2018) - Ahmad, F.; Shah, K.; Umair, M.; Jan, A.; Irfanullah,; Khan, S.; Muhammad, D.; Basit, S.; Wakil, S. M.; Ramzan, K.; Ahmad, W.
Abstract: Click here for the corresponding questions to this CME article.